Integration, ambivalence, and mental conflict - Brunning, L (2015)
In my DPhil thesis I critique a philosophical ideal of mental organization: that one’s mind ought to be integrated, that is, lack conflicts or ambivalence between mental states, because disintegration is argued to impair one’s agency and undermine one’s well-being. My argument has three parts. In part one, I describe Plato’s maximalist version of the ideal where, if ideally organized, one’s psyche lacks conflicts because one’s rational faculty, aware of what is valuable, harmonises one’s motivational and affective states. I also argue that any dispute about integration is orthogonal to the dispute between value monists and value pluralists. In part two, I contest the integration ideal by criticizing three manifestations of it in contemporary philosophy. I focus on the organization of desire, and on deliberative and affective ambivalence. My arguments have a similar structure. First, I challenge the link between the integrated mind and the purported benefits of unimpaired agency and well-being. On investigation, this apparent connection is largely contingent. Not all conflicts or ambivalence are harmful, and other social or psychological factors are relevant in case where they really are damaging. Secondly, I argue that there are contexts where integration is a form of mental rigidity or harmful impoverishment. Thirdly, I argue that being disintegrated seems morally good in some situations where one manifests fitting states of mind, particularly emotions. In part three, I ask whether integration can be reinterpreted to salvage an alternative ideal. After rejecting a promising candidate found in Kleinian psychoanalytic theory, I offer my own account of integration as a two-part capacity to tolerate difficult mental states (not necessarily bad mental states - excitement can be hard to tolerate), and to avoid being reflectively passive as one’s mental organization changes. This capacity has rational and non-rational elements. Finally, I consider how this reinterpreted capacity relates to the practice of virtue. I conclude that integration is not a virtue, and may be compatible with some viciousness, but it enables one to be virtuous in situations where there are pressures towards being insensitively singleminded.